Yield and water use efficiency of cowpea under water deficit - Paulo J. O. P. Souza; Thaynara F. Ramos; Lucilene de C. S. Fiel; Vivian D. da S. Farias; Denis de P. Sousa; Hildo G. G. C. Nunes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The state of Pará is the main regional producer of cowpea, but its yield is still low compared to other states of the Northern region such as Amazonas and Tocantins, due to the management adopted and the water regime during the cycle, since its cultivation is conducted on a rainfed basis. The objective of this study was to evaluate how water deficit imposed during reproductive stage interferes in the yield of cowpea and in its water use efficiency under the climatic conditions of Castanhal, Pará, Brazil, for agricultural planning purposes. The experiment was carried out in Castanhal, northeastern region of the Pará state during the dry season of 2014, 2015 and 2016. The experimental design was randomized blocks with six blocks and four treatments, corresponding to different irrigation depths in the reproductive stage, defined as 100, 50, 25 and 0% of the crop evapotranspiration. Water use efficiency (WUE) was determined by the ratio between total grain yield and total water used in each treatment. Maximum water availability led to an average increase in yield of 58% compared to the treatment without irrigation. Water depths below 260 mm limited yield to values lower than 1,000 kg ha-1. The cultivar adopted had WUE of 4.63 kg ha-1 mm-1, in response to the higher levels of water supply, but showed WUE of 4.31 kg ha-1 mm-1 under water depth of 50% of water demand.